2018
DOI: 10.1002/jgh3.12069
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with a low FODMAP diet in Asian patients with irritable bowel syndrome

Abstract: BackgroundThe efficacy and acceptance of a low fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) diet in Asian adults with irritable bowel syndrome (IBS) remain uncertain. We aimed to describe our early experience in a single center with a dedicated gastroenterology dietetic service.MethodsConsecutive patients with IBS referred to our dedicated Dietetic Gastroenterology Clinic between February 2016 and May 2016 were screened. A low FODMAP diet was instituted as per standard prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…In addition, because most of the education resources are in English, they are not easily accessible for health professionals in some Asian countries with low English proficiency. A study in Malaysia also indicated that adherence to low FODMAP diet may also be a challenge; thus, this dietary advice requires close follow up and, potentially, patients’ motivation …”
Section: Methodsmentioning
confidence: 99%
“…In addition, because most of the education resources are in English, they are not easily accessible for health professionals in some Asian countries with low English proficiency. A study in Malaysia also indicated that adherence to low FODMAP diet may also be a challenge; thus, this dietary advice requires close follow up and, potentially, patients’ motivation …”
Section: Methodsmentioning
confidence: 99%
“…Seven studies were conducted in the UK (31)(32)(33)(34)(35)(36)(37), seven in the USA (38)(39)(40)(41)(42)(43)(44) and one in Malaysia (45). Study design varied and included six case-controlled studies (34,35,39,40,42,44), three survey-based studies (32,33,38,41,43), three qualitative studies (31,36,37), and one cohort study (45); focussing on IBD (31,(33)(34)(35)(36)(37)(39)(40)(41)(42)44), IBS (43,45), prostate cancer (including bowel-related side-effects of treatment) (38) and coeliac disease (32). Studies recruited participants from various ethnic minority groups including South Asians, African Americans, Blacks, Hispanics, and Chinese.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Based on CASP and CEBMa quality criteria, there were seven good (four star) quality studies (31,(35)(36)(37)40,42,45), and eight moderately good (three star) quality studies (33,34,38,39,41,43,44).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In Malaysia, a small study on 16 adults with IBS found that only 50% of them were able to comply with the low FODMAP diet for 6 weeks. However, among those who were able to comply, there was an excellent symptom response—a 60% improvement in abdominal pain, bloating and flatulence [ 49 ].…”
Section: Summary Of Findingsmentioning
confidence: 99%